A study on E-Government services in MYEG Services Berhad: customer perception of E-Government services quality / Ida Dayana Md Zin - Md Zin, Ida Dayana (Faculty of Business and Management, 2009)
Purpose The purpose of this paper is to study on how MYEG Services Berhad responds towards delivering the service quality to the public. Researcher has signaled the need for Service Quality framework and model of initiatives to explore ways in which strategic service quality can be integrated into business structures and processes in a sustainable way. Design/methodology/approach The approach consists of theory building by reviewing the literature and examining the gaps and limitations. Findings MYEG Services Berhad had a negative response towards the delivering of service quality as there are many drawbacks as well as weaknesses on their web site design and system implemented. This study suggests that the service quality framework set up by company is important towards a long-term development as it depends heavily on the nature of the programs, how the programs are designed and implemented, as well as the composition of the beneficiary communities. Research limitation/implication The study is limited by the exclusive use of quantitative methods; the outcomes suggest that further, qualitative, research could be valuable in exploring user needs, motivations, competence, and level of political engagement Originality/Value The paper adds insight into customer perceptions toward the E-gGovernment services.